Manufacturing in the time of COVID-19: an assessment of barriers and enablers - Okorie, Okechukwu; Subramoniam, Ramesh; Charnley, Fiona; Widdifield, David; Patsavellas, John; Salonitis, Konstantinos (IEEE, 2020)
Pandemics and other forms of epidemic outbreaks are a unique case of manufacturing risk typified by high uncertainty, increasing propagation and long-term disruption to manufacturers, supply chain actors as well as the end-users and consumers. For manufacturing the COVID-19 disruption scope has been largely two-fold; an endogenous disruption of manufacturing processes and systems as well as extreme shifts in demand and supply caused by exogenous supply chain disruption. Existing literature on disruptions in manufacturing suggests that pandemics are qualitatively different from typical disruptions. There is no literature available to manufacturing practitioners that identify the barriers and enablers of manufacturing resilience, especially with regards to pivoting of the manufacturing sector in response to a pandemic. This study draws on an extensive survey collected during the COVID-19 pandemic. The respondents were employees of manufacturing firms in all regions of the world who had engaged in manufacturing during the pandemic or had opted out from manufacturing due to various identified reasons. By collating their responses, we offer to practitioners and policymakers an analysis for identifying a best-practice framework for pivoting successfully as a response to major manufacturing disruptions.
Keywords: manufacturing; manufacturing resilience; COVID-19; coronavirus; pivoting; digital technologies; pandemic; supply chain disruption